Forensic injury characteristics in explosive trauma mass case - D. A. Zotkin; M. A. Kislov; K. N. Krupin (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
The use of improvised explosive devices for terrorist purposes in crowded areas forms explosive trauma as a form of violent peacetime trauma. The forensic aspect of such events is associated with the reconstruction of explosion circumstances, in which the structure of organs and tissues damage of the body is important, as morphological equivalents of damaging factors impact. Based on the archival material of forensic medical examinations, identical mass cases of explosive trauma are summarized, in the assessment of which the characteristics of explosion damaging factors and the damage to the body corresponding to their effects are given, which can be used in forensic practice to establish the conditions and circumstances of the explosion, as well as the reconstruction of these events.